KETERSEDIAAN PRASARANA DAN SARANA PERMUKIMAN DI KECAMATAN SONDER - Rumagit, Lefrando J.; Waani, Judy O.; Rengkung, Michael M. (Department of Architecture, Engineering Faculty - Sam Ratulangi University, 2021)
Sonder sub-district is one of the districts that is included as a district growth center, namely the local activity center (PKL) in the 2014-2034 RTRW of Minahasa. As for the RTRW direction in article 5 paragraph 2 letter g, regarding increasing the availability and quality of infrastructure services and supporting facilities for urban and rural activities. This study will identify and analyze the availability of infrastructure and facilities for settlements in Sonder District based on SNI 03-1733-2004 supported by other existing standards. The analysis method used is descriptive qualitative method in identifying data by obtaining primary data through field observations, taking documentation, and interviews with sub-district and village governments, as well as quantitative descriptive methods in analyzing data, as well as spatial analysis methods to determine the distribution of infrastructure and settlement facilities. also as an analysis of the service radius of the facility. The results of the discussion show that there are some inadequate infrastructure and facilities such as road infrastructure and solid waste infrastructure. where road infrastructure, traffic lane widths are not up to standard, and solid waste infrastructure, TPS and local TPA are not yet available, so most people still throw garbage in any place, such as drainage, and rivers. For facilities, educational facilities still require an additional 6 units for kindergarten, and 1 unit for senior high schools.